Ambient Noise Levels and Wireless Headsets for Communication in Aerosolizing Otolaryngology Surgery During COVID-19. (October 2021) - Levin, Marc; Zhou, Kelvin; Sommer, Ethan C.; McHugh, Tobial; Sommer, Doron D.
The objective of this short scientific communication is to describe and test a strategy to overcome communication barriers in coronavirus disease 2019 (COVID-19) era otolaryngology operating rooms. Thirteen endoscopic sinus surgeries, 4 skull base surgeries, and 1 tracheotomy were performed with powered air-purifying respirators. During these surgeries, surgical team members donned headsets with microphones linked via conference call. Noise measurements and survey responses were obtained and compared to pre–COVID-19 data. Noise was problematic and caused miscommunication as per 93% and 76% of respondents, respectively. Noise in COVID-19 era operating rooms was significantly higher compared to pre–COVID-19 era data (73.8 vs 70.2 decibels, P = .04). Implementation of this headset strategy significantly improved communication. Respondents with headsets were less likely to encounter communication problems (31% vs 93%, P < .001). Intraoperative measures to protect surgical team members during aerosolizing surgeries may impair communication. Linking team members via a conference call is a solution to improve communication.